Diversity and Continuity. How Did Ferdinand de Saussure Teach Linguistic Practices? - Mejía Quijano, Claudia; Restrepo Montoya, Natalia; Salleg Carvajalino, Andrés (Íkala, Revista de Lenguaje y Cultura, 2009)
<!– [if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!– [if gte mso 9]> <![endif]–><!– [if gte mso 10]> <![endif]–> This paper presents a reflection on the results of the research project, "Practice and Theory in Ferdinand de Saussure," conducted at the University of Antioquia. We state the objective of the study, describe the materials and methodology used and the stages of the project, and relate the results of Saussure’s linguistic practices as a teacher to his general theory of language. In this way, we demonstrate that Saussure’s specific theory is actually linked to his practical knowledge regarding the teaching of translation and of the Sanskrit language. Received: 04-02-09 /Accepted: 10-06-09 How to reference this article: Mejia Quijano, C., Restrepo Montoya, N. & Salleg Carvajalino, A. (2009). Diversidad y continuidad ¿Cómo enseñaba prácticas idiomáticas Ferdinand de Saussure?. Íkala.14(3), pp.87-114.